2014
DOI: 10.1371/journal.pone.0096356
|View full text |Cite|
|
Sign up to set email alerts
|

Continuity in a VA Patient-Centered Medical Home Reduces Emergency Department Visits

Abstract: BackgroundOne major goal of the Patient-Centered Medical Home (PCMH) is to improve continuity of care between patients and providers and reduce the utilization of non-primary care services like the emergency department (ED).ObjectiveTo characterize continuity under the Veterans Health Administration’s PCMH model – the Patient Aligned Care Team (PACT), at one large Veterans Affair’s (VA’s) primary care clinic, determine the characteristics associated with high levels of continuity, and assess the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…The available literature indicated that ED use should decline for chronically ill populations with PCMH concordant care. 16,44,45 Lack of an association between PCMH concordant care and any ED visit in this study is consistent with the available literature that indicate no impact for patients without chronic conditions and patients seen in small individual practices. Lack of association might be due to inherent limitations of cross-sectional analyses.…”
Section: Discussionsupporting
confidence: 89%
“…The available literature indicated that ED use should decline for chronically ill populations with PCMH concordant care. 16,44,45 Lack of an association between PCMH concordant care and any ED visit in this study is consistent with the available literature that indicate no impact for patients without chronic conditions and patients seen in small individual practices. Lack of association might be due to inherent limitations of cross-sectional analyses.…”
Section: Discussionsupporting
confidence: 89%
“…PCMH providers can conduct needs assessments for these patients, develop individualized care plans, and reach out to members of the “medical neighborhood” to coordinate medical and social services . Some PCMH evaluations have shown reduced ED utilization among PCMH patients although no studies have examined the impact of a PCMH transformation on frequent ED visitors. “Super utilizer” care management programs are also increasingly common and vary in their level of integration with primary care.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The Veterans Health Administration Patient Aligned Care team found that patients with a PCP had a 45% lower emergency department ED utilization rate. [11] WESTMED Medical Group who participated in the Aetna PCMH Program earned over $300,000 in incentive payments in the first year with 35% reduction in hospitalization. [12] Although a number of organizations recognize PCMH status, the National Committee for Quality Assurance (NCQA) is the recognition most often used.…”
Section: Pcmhmentioning
confidence: 99%